Can Platelet Count and Mean Platelet Volume be Used as Markers of Postdural Puncture Headache in Obstetric Patients?. (7th August 2020) - Uzundere, Osman; Kaçar, Cem Kıvılcım; Kaya, Sedat
Abstract : Objective . In this study, considering the importance of platelet function in inflammatory processes, we explored whether there are relationships of platelet indices with postdural puncture headache (PDPH) and pain developing after use of spinal needles and whether patient characteristics contribute to the development of PDPH. Methods . This prospective, observational study included 76 patients (Group 1) with PDPH and 93 patients (Group 2) without PDPH. The postoperative hemoglobin, hematocrit, platelet count (PC), and mean platelet volume (MPV) values were recorded, along with age, blood type, Rh factor, gravida, parity, and gestational age. In addition, the time of the onset of pain was recorded in patients who complained of a postspinal headache. Results . Hemoglobin and hematocrit values in Group 1 were significantly lower than in Group 2 (both, p = 0.024 ). The PC of Group 1 was significantly higher than that of Group 2 (p < 0.001 ), whereas the MPV was significantly lower (p < 0.001 ). The area under the curve (AUC) values were significant for hemoglobin, hematocrit, PC, and MPV (p = 0.022, p = 0.024, p < 0.001, and p < 0.001, resp.). For MPV, the AUC value was 0.293, sensitivity was 1%, and specificity was 99%. The highest likelihood ratio (LR+) value was 1.22 at a cut-off value of 13.3 fL. For the PC, the AUC value was 0.666, the sensitivity was 9%, and the specificity was 99%, while the highest LR + value was 8.56 at a cut-off value of 352 × 10 9 /L. There was no significant relationship between the parameters examined and the onset of pain. Conclusion . In this study, the PC was higher and MPV was lower in obstetric patients with PDPH compared with the control group. However, we also found that these two values cannot be used as markers of PDPH.